KESUKAAN MASYARAKAT TERHADAP PEMBUATAN BROWNIES BERSUBSTITUSI TEPUNG KULIT ARI KACANG KEDELAI - Yeni Tustiana; Rina Setyaningsih (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2020)
This study aims to determine, (1)The effect of the Soybean Skin Flour percentage of 15%, 30%, and 45% against the quality brownies are reviewed from the aspect of texture, color, aroma and flavor. (2) The quality of the brownies corresponds to the percentage 15%, 30%, and 45% seen from the level of Community preference. This type of research is pure experimentation. Population: peanut flour, soybeans. Samples: The peanut flour of soybean is 15% percentage, 30%, and 45%. Data collection method in the form of organoleptic chemical test of product, questionnaire and documentation. Trials of hedonic instruments and organoleptic research were conducted on 36 panelists. Data tested validity of the group Experiment Design (RAK), ANOVA one lane and the smallest real difference formula (BNT). The Results show (1) Brownies substitutions of Soybean Skin Flour effect on the results of Brownies with the properties of organoleptic percentage of 15% thick dark brown color, flavor chocolate, skin flour, aroma brown and typical of the skin, soft texture, porous and the outer texture of crusty dry). Percentage 30% brown color is less dense, taste less brown, aroma less chocolate aroma, less soft texture, and less crusty outer texture. Percentage 45% produce a pale color color score), too much sense of skin, aroma is too dark, texture in less soft, outer texture is less dry. Soybean flour Brownies skin substitution 15% substitutions with very fond criteria and just like the original brownies. (2) The highest protein nutrient content on the 45% Brownies percentage, with a protein content of 6.85%, and the highest crude fiber content at 15% percentage with a content of 2.08%. From several percentage above the opinion of the expert panelist and the community liked the brownies with a substitution of 15%.